VD_FINDINFO HC / 2017 / 286 vom 27. März 2017 - VD Tribunal cantonal (2017)
INVENTAIRE, DÉCISION D'IRRECEVABILITÉ, DROIT DES SUCCESSIONS, VOIE DE DROIT PRÉMATURÉE | 553 CC, 321 CPC (CH), 322 al. 1 CPC (CH)